Understanding masculinity in Turkey through the films of male auteur directors - Hasan Gürkan; Işıl Yarcı (CINEJ Cinema Journal, 2023)
This study focuses the representation of male characters in the films of contemporary male auteur directors in Turkey. Once Upon a Time in Anatolia (Zeki Demirkubuz, 2011), Underground (Demizkubuz, 2012), and Big World (Erdem, 2016) are explored using sociological film analysis. Unlike mainstream cinema, the protagonists in these directors’ films do not demonstrate hegemonic masculinity; the supporting male characters that do demonstrate hegemonic masculinity category are not white Turks. Arguably, the male characters embody a new hybrid hegemonic masculinity that combines various masculinities to reproduce patriarchy. It can be stated that “Others” in these films are negatively affected.